The occlusal wear of ceramic fixed dental prostheses: 3-Year results in a randomized controlled clinical trial with split-mouth design - Seidel, Anna; Belli, Renan; Breidebach, Nathalie; Wichmann, Manfred; Matta, Ragai (Journal of Dentistry, 2020)
Objectives: This study's hypothesis was to evaluate differences of the occlusal wear rate for monolithically fabricated lithium disilicate and hand-veneered zirconia crowns in-vivo. Furthermore, a comparison of the materials' clinical performance according to CDA criteria was investigated.
CRIS-Team WoS Importer:2021-01-15